Optimalisasi Penggunaan Aplikasi Digital Payment bagi Pedagang Pasar Tradisional - Fatihanursari Dikananda; Dodi Solihudin; Anjar Ayuning Lestari; Athhar Hafizha Luthfi (CV. Multi Kreasi Media, 2022)
This Community Partnership Program aims to optimize the use of digital payment applications among traditional market traders. Activities include education on the benefits of digital payment, training on application usage, and assistance in non-cash transactions. This program is expected to increase transaction efficiency, security, and financial accessibility for traders, while also promoting financial inclusion in traditional markets.